Finescale Structure of the Temperature-Salinity Relationship - Ferrari, Raffaele; Polzin, Kurt L (2003)
The long term goal of this project is to understand the processes that establish the temperature-salinity relationship in the ocean, with emphasis on the interplay between advection at the large scale, eddy stirring at the mesoscale and turbulent mixing at the finescale. The objectives of this proposal are (1) to unfold the processes that participate in the creation of the temperature-salinity relationship in two high-resolution data sets, the North Atlantic Tracer Release Experiment (NATRE) and the Salt Finger Tracer Release Experiment (SFTRE), and (2) to determine the relative importance of eddy stirring and turbulent mixing process in the ocean interior with a combination of numerical and theoretical tools. Prepared in cooperation with Woods Hole Oceanographic Institution, Woods Hole, MA.